2021
DOI: 10.18273/revion.v34n2-2021003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la producción de aceite crudo de palma y palmiste en el norte de Colombia mediante el análisis de exergía asistido por computador

Abstract: Palm production chains in Colombia have some unsatisfied demands that affect their competitiveness. Specific demands include efficiency in energy use. Therefore, in the present report, an exergy analysis for the dual crude palm and kernel oil production process was carried out to determine the main energy sinks and suggest technological improvements that allow better use of energy. For this study, the process was initially simulated in the Aspen Plus ® software, where the chemical and physical exergies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…This phenomenon may also be observed in the infection and virus adaption (stage 2) and centrifugation stages (stage 4) where the second and third highest irreversibilities (132.26 and 64.28 MJ/h, respectively) were obtained. This finding agrees with the research performed by Moreno et al [31], which found that centrifugation was one of the most critical stages in the production of crude palm kernel oil due to the energy required in the stage. Regarding the exergy of waste, the highest value was obtained in the centrifugation stage (57.27 MJ/h) because cellular debris is removed in this stage.…”
Section: Exergy Analysissupporting
confidence: 93%
“…This phenomenon may also be observed in the infection and virus adaption (stage 2) and centrifugation stages (stage 4) where the second and third highest irreversibilities (132.26 and 64.28 MJ/h, respectively) were obtained. This finding agrees with the research performed by Moreno et al [31], which found that centrifugation was one of the most critical stages in the production of crude palm kernel oil due to the energy required in the stage. Regarding the exergy of waste, the highest value was obtained in the centrifugation stage (57.27 MJ/h) because cellular debris is removed in this stage.…”
Section: Exergy Analysissupporting
confidence: 93%
“…Urea was the substance with the maximum dangerous substance subindex due to the threshold limit value (10 ppm) [29]. On the other hand, Figure 3 shows that the equipment safety subindex was the majority contributor to the process safety index because of the reactor presence, which means an equipment safety subindex of 3, according to this methodology developed by [21]. The above implies that precautions should be established in the reactor system to decrease the potential hazards associated with the equipment and increase the safety of the process as runaway reactions, control of the temperature in exothermic reactions, undesired reactions, increases in pressure by the presence of CO 2 , among others, and to increase the safety of the process.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used for calculating energy indicators was the exergy analysis, which is based on thermodynamics' first and second laws. Exergy analysis provides information about thermodynamic inefficiencies of a process [21]. This tool identifies critical stages in the process; therefore, energy improvements may be proposed.…”
Section: Exergy Indicatorsmentioning
confidence: 99%